Oral health care parameters: comparison between two methods of scheduling clinical dental care in the public service - doi: 10.5020/18061230.2012.p255 - Artênio José Ísper Garbin; Cléa Adas Saliba Garbin; Suzely Adas Saliba Moimaz; Tânia Adas Saliba Rovida; Diego Garcia Diniz (Universidade de Fortaleza, 2012)
Objective: To compare two forms of scheduling clinical dental care for the oral health teams (OHT) included in the strategy of family health, regarding productive aspects of assistance. Methods: Two OHT worked concurrently, using two methods of clinical care: the parameter recommended by the Ministry of Health Ordinance No. 1101, 2002, which establishes 03 dental visits per hour (c/h) per team, and a Testing model, with 02 c/h, being each method applied for a period of 615 hours. The quantitative data was collected in OHTs' daily production spreadsheets, covering the following items: the number of dental visits (initial, for maintenance and for emergency procedures), procedures performed, consumption of material and sterilization cycles. Data was compared and statistically analyzed through the BioStat 5.0 by applying the paired t-test (p <0.05). Results: Under the Ministerial method and the Testing model, were performed, respectively, 288 and 365 first dental visits, 921 and 686 return dental visits, 167 and 172 emergency dental attendances, with 469 and 110 fouls, 212 and 327 treatments were finished and 2501 and 3046 dental procedures were realized. Among eleven analyzed consumables, five were consumed in smaller quantities in the Testing model: gloves (9%), anesthesia (38%), anesthetic needle (34%), suture material (24%) and aspirators (11%), while the six remaining items presented similar consumption rates between the two models. Conclusions: The testing model revealed to be more productive and economical